Luck - "Hazarika, Dhruba" (Gurgaon, 2009)
Wild tales with a difference?Hazarika?s empathy with all creatures great and small comes through in these absorbing, spare and often deeply moving stories. Life in the forests and small towns of Assam is brought vividly to life by a gifted writer.?
Keywords: Fiction